ASSESSMENT OF Fe, Cu, Zn, Pb, Cd & Hg IN AMBON BAY SURFACE SEDIMENTS - Manullang, Corry Yanti; Lestari, -; Tapilatu, Yosmina; Arifin, Zainal (Marine Research in Indonesia, 2017)
In this study, the concentration of Fe, Cu, Zn, Pb, Cd and Hg were determined in marine surface sediment to assess the impact of pollution sources around the Ambon Bay by application of Atomic Absorption Spectrometry (AAS). The metals concentrations found were in the following ranges (in mg kg-1 DW): 27,598 to 51,716 for Fe, 13.7 to 44.8 for Cu, 51.3 to 163 for Zn, 0.1 to 0.66 for Cd, 0.04 to 0.44 for Hg and 14.4 to 24.5 for Pb. The results indicated the strong contribution of heavy metals pollution from the urban waste, residential sources, farming industry, shipping activities and ship repair activity from dockyard around the Ambon Bay. This study provides the most updated information regarding heavy metals (Fe, Cu, Zn, Pb, Cd and Hg) concentrations in Ambon Bay marine sediment.